Rapid and sensitive determination of shikonin and its derivatives in the roots of Arnebia euchroma (Royle) Johnst using matrix solid-phase dispersion extraction and ultrahigh-performance liquid chromatography with photodiode array detector. Issue 9 (28th May 2018) - Zhang, Qi; Cai, Defu; Wang, Liang; Yang, Xueting; Fan, Songjie; Zhang, Keyong
Abstract: A rapid, efficient, and eco-friendly method for the extraction and determination of shikonin and its derivatives in the roots of Arnebia euchroma (Royle) Johnst ( A. euchroma ) was presented based on matrix solid-phase dispersion (MSPD) extraction and ultrahigh-performance liquid chromatography (UPLC) coupled with photodiode array detector (DAD). The experimental conditions that affected the extraction performance, including the type of dispersant, the mass ratio of sample to the dispersant, the type of elution solvent and volume of elution solvent were investigated and optimized. The optimal MSPD conditions were determined to be that C18 was served as a dispersant, the ratio of sample/C18 was selected to be 1:3, and 5.0 mL of ethanol was chosen as the elution solvent. Under these optimal conditions, the proposed method exhibited good linearity ( r 2 ≥ 0.9995), with the limits of detection (LODs) in the range of 33.0–233.6 ng/g and excellent precision (RSD ≤1.8%). And satisfactory recoveries were above 91.4% at all three concentration levels. Compared with other reported methods, this proposal method was more convenient and time-saving with reduced requirements on the amount of sample and solvent. Finally, the methodology was successfully applied to the extraction and determination of shikonin and its derivatives in the roots of A. euchroma . Graphical Abstract: